(untitled) (Interfaces: A Journal of Medieval European Literatures, 2024)
This paper argues for a modest expansion of the concept of occasional verse in the context of classical Persian poetry. Discussion of occasionality in this field has traditionally focused on the panegyric ode (qaṣīda), and to a lesser degree on the epigrammatic poem (qiṭʿa). While these forms certainly represent key categories of occasional verse, it is unfortunate that the type of poetry that came to dominate the classical Persian tradition – i.e., love lyric, especially the ghazal – has less of a clear position in the discourse on occasionality. The difficulty in considering ghazals as occasional is, admittedly, first and foremost a result of their tendency to treat abstract themes, rather than to comment on specific events. What I suggest, however, is that we can look to biographical anthologies of poets (taẕkiras) – in particular from the early modern period – since they sometimes offer anecdotes to explain the context underlying the composition and sharing of ghazals. Leveraging these sources could allow us to extend the study of occasional verse in Persian to a much larger body of poetry, with strong representation from all historical periods.